Stability constraints for oceanic numerical models: implications for the formulation of time and space discretizations. (August 2015) - Lemarié, F.; Debreu, L.; Madec, G.; Demange, J.; Molines, J.M.; Honnorat, M.
Highlights: It is essential to study numerical schemes in a space–time approach to get accurate estimate of the CFL criteria. Time-step of eddying global models with an Eulerian vertical coordinate is often restricted by vertical advection. Space–time discretizations must be robust and stable for advection and diffusion to maintain good efficiency. Coupled space–time schemes offer an efficiency factor that is unrivaled especially when high-order accuracy is required. Abstract: Except for vertical diffusion (and possibly the external mode and bottom drag), oceanic models usually rely on explicit time-stepping algorithms subject to Courant–Friedrichs–Lewy (CFL) stability criteria. Implicit methods could be unconditionally stable, but an algebraic system must be solved at each time step and other considerations such as accuracy and efficiency are less straightforward to achieve. Depending on the target application, the process limiting the maximum allowed time-step is generally different. In this paper, we introduce offline diagnostics to predict stability limits associated with internal gravity waves, advection, diffusion, and rotation. This suite of diagnostics is applied to a set of global, regional and coastal numerical simulations with several horizontal/vertical resolutions and different numerical models. We show that, for resolutions finer that 1/2°, models with an Eulerian vertical coordinate are generally constrained by vertical advection in a few hot spots and that numerics must be extremely robust to changes in Courant number. Based on those results, we review the stability and accuracy of existing numerical kernels in vogue in primitive equations oceanic models with a focus on advective processes and the dynamics of internal waves. We emphasize the additional value of studying the numerical kernel of oceanic models in the light of coupled space–time approaches instead of studying the time schemes independently from spatial discretizations. From this study, we suggest some guidelines for the development of temporal schemes in future generation multi-purpose oceanic models.